Performance in Ancient and Medieval Judaism - Khan, Geoffrey 1958-; Najman, Hindy 1967- (2022)
This article explores the performance of Jewish sacred textual traditions. Performance, as we define it, is both textual and oral and works dynamically between the two. In the Second Temple period, we show the variety of performance which embodies the vitality of the texts. Performance is a feature of scribal practice and liturgy (e.g., Hodayot). It draws on existing text to create something new (e.g., Apostrophe to Zion). From the Second Temple period into the Middle Ages, we see continued pluriformity in the oral performance of the written text of the Hebrew Bible. Creativity is evident across oral and material representation. The texts discussed throughout this article remained dynamic and diverse. The focus and scope of this article also prepares for many of the ideas picked up by the essays which follow in this volume.
Keywords: reading traditions; Masoretic Text; Tiberian tradition; Orthography; Vitality; textual performance; oral performance; Liturgy